The periodontal pathogen, Porphyromonas gingivalis , and the participatory role of caspase-1 in the progression of atherosclerosis - Gage, Jessica (University of Ottawa (Canada), 2008)
Porphyromonas gingivalis, a key pathogen in periodontal disease, promotes atherosclerosis in apolipoprotein E null (apoe-/-) mice, a well characterized mouse model of the disease. Previous studies have provided indirect evidence that P gingivalis is capable of activating the enzyme caspase-1 in vitro, while preliminary studies conducted by our laboratory have outlined a role for caspase-1 in atherosclerosis in apoe-/- mice. The present study provides direct evidence that P gingivalis is capable of activating caspase-1, and that P gingivalis is capable of gaining access to, and localizing at, sites of lesion development following an oral challenge. Oral infection with P gingivalis exacerbated the development of atherosclerosis in the aortic root of male mice competent for caspase-1 as compared to those deficient in the enzyme. Infected animals also displayed evidence of alveolar bone loss, a hallmark of periodontal disease. Our findings reveal that oral infection with P gingivalis accelerates atherosclerotic lesion development in male apoe-/- mice through the activation of caspase-1.
Keywords: Biology, Molecular.; Health Sciences, Dentistry.